Optimizing E-Government for Enhanced Transparency and Accountability in Local Governance - Dwibin Kannapadang; Siti Munawaroh; Sayugo Adi Purwanto (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Optimizing e-Government has become crucial for local governments to improve public service delivery, enhance transparency, and strengthen accountability in the digital era. This study aims to analyze the influence of e-Government optimization on improving transparency and accountability in local governments in Indonesia. The research is driven by the growing importance of digital bureaucracy systems in realizing open and responsible governance. A quantitative explanatory approach was employed, involving 150 respondents from five local governments that have implemented the electronic-based government for at least three years. The research instrument was developed using Electronic-Based Government System indicators and analyzed through Structural Equation Modeling e-CRM Partial Least Squares (SEM-PLS). The findings show that e-Government optimization has a positive and significant impact on both transparency (path coefficient = 0.67; R² = 0.58) and accountability (path coefficient = 0.72; R² = 0.64) at a 5% significance level. These results suggest that successful e-Government implementation encompassing technological infrastructure, system interoperability, managerial support, user competence, and digital service quality meaningfully contributes to information openness and public accountability. This study offers theoretical contributions to the literature on e-Governance and practical insights for local governments in designing effective, inclusive, and sustainable digital strategies.